Cascade enzymes within self-assembled hybrid nanogel mimicked neutrophil lysosomes for singlet oxygen elevated cancer therapy - Qing Wu (Nature Portfolio, 2019)
Enzymatic reactions caused by neutrophils can cause the elevation of reactive oxygen species (ROS) in tumour tissue, Here, the authors, inspired by the neutrophils, design and test a synthetic cascade reaction which turns ROS into singlet oxygen and demonstrate the application of the designed nanoparticle